Percutaneous endoscopic gastrostomy in children: a single center study at Tertiary hospital Iran - Mohsen Dehghani, Seyed (2018)
Introduction: The aim of this study was to evaluate complications after percutaneous endoscopic gastrostomy among children who underwent percutaneous endoscopic gastrostomy in Nemazee hospital. Materials and methods: All children who underwent percutaneous endoscopic gastrostomy were included in the current study. Place of the study was department of pediatric gastroenterology of Nemazee children hospital of Shiraz university of medical sciences. Duration of the study was 5 year starting from 2008. All drugs such as aspirin, NSAIDS, and heparin were discontinued 1-7 days before procedures. All patients were kept NPO 6-8 hours before procedure according to the age. Single dose antibiotic was prescribed for all cases before procedure. During procedure, all patients were sedated using propofol and or midazolam. Some patients required intubation. Results: Of 39 cases who underwent PEG, 4 (10.2%) patients showed complication. The most common indication for PEG insertion were neurologic problem (84.6%) and metabolic disease (10.2%). Of our patients, 84.6% of the cases had the weight below third percentile. Conclusion: The most common indication for percutaneous endoscopic gastrostomy was cerebral palsy. The complication rate in our study was 10.2%. Celulitis was the most common complication.